Effectiveness Of Permenkes RI Number 85 of 2019 On Dak In The Field Of Physical Health In Puskesmas Randangan - Bayu Reksa Pakaya (Universitas Negeri Gorontalo, 2019)
Abstract: The effectiveness of a rule must be measured as long as the law or rule applies and the extent to which it runs after it is enforced. This is an evaluation step to review the extent to which the law applies. Permits for The Operation of Wastewater Management Installations as stipulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 85 of 2019 point 10 letter (l) which regulates the ownership permit of IPAL permit for Puskesmas. Health centers classified as inpatient health centers are required to have IPAL buildings and must have permission from the Environment Agency. Puskesmas Motolohu is a Puskesmas that is classified as an inpatient health center that must be IPAL. Puskesmas Motolohu has been operating IPAL since 2016 but does not have a permit until 2021. Supposedly since the construction of IPAL in Motolohu Health Center in 2016 already has a permit from the Environment Office of Pohuwato Regency. Because of the violation, the Environment Office of Pohuwato Regency has issued a written reprimand sanction to the Motolohu Health Center. The enactment of administrative sanctions is a step so that the rules on IPAL Permits can be effective as they should be.Keywords: Effectiveness, IPAL Permissions